COMPANY PERFORMANCE AND ACHIEVEMENTS POST MERGER CASE STUDY OF PT INDOSAT TBK (IOH) - Ardi Wiranata Hutasoit; M. Yusuf Sirat; Roy Erisusanto; Faisal; Suzan Novita; Indrayani; Muammar Khaddafi (RADJA PUBLIKA, 2023)
Mergers and Acquisitions (M&A) is a strategy commonly used by companies to achieve growth, expand market share, gain access to new technologies, and achieve competitive advantage. However, the M&A process does not always go according to plan and can present complex challenges. Many companies have failed in conducting mergers and acquisitions, which has an impact on organizational performance and shareholder value. Therefore, it is very important to understand the factors that influence the success and failure of this process, especially in the context of a telecommunications company such as PT Indosat Tbk (IOH). The literature shows that there are many factors that contribute to the success or failure of mergers and acquisitions. These factors include clear strategy and objectives, effective operational integration, management of organizational culture, strong leadership, effective change management, human resource management, and external factors such as market conditions and regulations. It is important for companies to carefully consider and manage these factors in their mergers and acquisitions processes. The case study of PT Indosat Tbk (IOH) is the focus of this research article. The company has experienced mergers and acquisitions in its history, namely with PT Hutchison 3 Indonesia (H3I) or Tri Indonesia. Therefore, analyzing the factors that influence the success and failure in PT Indosat Tbk (IOH) mergers and acquisitions can provide valuable insights for other companies planning M&A in the future. This study uses a qualitative approach by collecting data through relevant literature studies, financial reports, and company publications. The collected data is then analyzed systematically to identify the factors that influence the success and failure of mergers and acquisitions at PT Indosat Tbk (IOH). The findings of this study are expected to provide insight and better understanding of company performance and post-merger acquisition achievements, especially in the context of PT Indosat Tbk (IOH). With a better understanding, companies can take the right steps to increase the chances of success in the M&A process.